Fostering environmental knowledge and action through online learning resources - Carmen Daniela Maier (Stockholm University Press, 2010)
In order to secure understanding of environmental issues, to promote behavioral change and to encourage environmental action, more and more educational practices support and provide environmental programs. This article explores the design of online learning resources created for teachers and students by the GreenLearning environmental education program. The topic is approached from a social semiotic perspective. I conduct a multimodal analysis of the knowledge processes and the knowledge selection types that characterize the GreenLearning environmental education program and its online discourse. The multimodal analysis aims at identifying what types of knowledge and knowledge processes are communicated. The impact of knowledge processes upon the transformation of learning's forms and purposes, students' roles and environment's function is then examined. The analysis also aims to show how the new learning design addresses the expertise of multiliterate students allowing for diverse forms of engagement and interaction when fostering environmental knowledge and action.